FACTORS INFLUENCING WILLINGNESS TO CONTRIBUTE IN CASH WAQF: CASE OF SOUTH TANGERANG, INDONESIA - Hudzaifah Ahmad (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2019)
Abstract: Factors Influencing Willingness to Contribute in Cash Waqf: Case of South Tangerang, Indonesia. Waqf has long been the backbone of community service in Indonesia, especially in the fields of religion and education. Considering the importance of waqf in the socio-economic field in Indonesia, the government expanded the scope of waqf which was originally only in the form of fixed assets and then added with movable assets such as money. As a country with the largest Muslim population in the world, Indonesia has a huge cash waqf potential. But this potential has not been able to be optimized by the government or the private sector. The problem of the lack of awareness of Muslims in Indonesia about cash waqf is the main obstacle. There are several factors that influence one's willingness to do cash waqf, namely knowledge, income, social culture, and promotion. To determine the influence of these factors, the data obtained from respondents from the survey instrument adopted were subjected to descriptive analysis statistical analysis. The findings indicate that all factors significantly affect a person's willingness to do cash waqf. Recommendations contingent on research findings were offered.  Abstrak. Faktor-Faktor yang Mempengaruhi Kesediaan untuk Berkontribusi dalam Wakaf Tunai: Kasus Tangerang Selatan, Indonesia. Wakaf telah lama menjadi tulang punggung pengabdian masyarakat di Indonesia, khususnya di bidang agama dan pendidikan. Mengingat pentingnya wakaf dalam bidang sosial ekonomi di Indonesia, pemerintah kemudian memperluas cakupan wakaf yang semula hanya berupa aset tetap menjadi ditambah dengan aset bergerak seperti uang. Sebagai negara dengan populasi Muslim terbesar di dunia, Indonesia memiliki potensi wakaf tunai yang besar. Tetapi potensi ini belum dapat dioptimalkan oleh pemerintah atau sektor swasta. Masalah kurangnya kesadaran umat Islam di Indonesia tentang wakaf tunai adalah kendala utama. Ada beberapa faktor yang mempengaruhi kemauan seseorang untuk melakukan wakaf tunai, yaitu pengetahuan, pendapatan, sosial budaya, dan promosi. Untuk menentukan pengaruh faktor-faktor ini, data yang diperoleh dari responden dari instrumen survei yang diadopsi menjadi sasaran analisis deskriptif analisis statistik. Temuan menunjukkan bahwa semua faktor secara signifikan mempengaruhi kesediaan seseorang untuk melakukan wakaf tunai. Rekomendasi yang bergantung pada temuan penelitian ditawarkan.